2018
DOI: 10.1002/2017sw001738
|View full text |Cite
|
Sign up to set email alerts
|

Gigantic Circular Shock Acoustic Waves in the Ionosphere Triggered by the Launch of FORMOSAT‐5 Satellite

Abstract: The launch of SpaceX Falcon 9 rocket delivered Taiwan's FORMOSAT‐5 satellite to orbit from Vandenberg Air Force Base in California at 18:51:00 UT on 24 August 2017. To facilitate the delivery of FORMOSAT‐5 to its mission orbit altitude of ~720 km, the Falcon 9 made a steep initial ascent. During the launch, the supersonic rocket induced gigantic circular shock acoustic waves (SAWs) in total electron content (TEC) over the western United States beginning approximately 5 min after the liftoff. The circular SAWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 67 publications
5
29
0
Order By: Relevance
“…The initial parameters at 15:00 UT of the second day are then used to initialize the SAMI3/ESF. Nevertheless, these impulsive waves displaying a nonlinear wave pattern (N-shape) in vertical TEC profiles (not shown) are likely associated with the shock waves (e.g., Astafyeva et al, 2013;Zettergren et al, 2017), which are commonly observed during the rocket ascending (e.g., Afraimovich et al, 2002;Chou et al, 2018;Ding et al, 2014;Kakinami et al, 2013;Lin et al, 2014;. The longitude is limited to 6°with periodic boundary conditions for computing the potential and is centered at 3°so the universal time and local time are the same.…”
Section: Sami3/esf Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial parameters at 15:00 UT of the second day are then used to initialize the SAMI3/ESF. Nevertheless, these impulsive waves displaying a nonlinear wave pattern (N-shape) in vertical TEC profiles (not shown) are likely associated with the shock waves (e.g., Astafyeva et al, 2013;Zettergren et al, 2017), which are commonly observed during the rocket ascending (e.g., Afraimovich et al, 2002;Chou et al, 2018;Ding et al, 2014;Kakinami et al, 2013;Lin et al, 2014;. The longitude is limited to 6°with periodic boundary conditions for computing the potential and is centered at 3°so the universal time and local time are the same.…”
Section: Sami3/esf Modelmentioning
confidence: 99%
“…In Figure 3 the ionospheric plasma hole has a TEC reduction of~2 TECU (Figures 3b and 3c), approximately 17% of the background TEC (~12 TECU, Figure 3a), and last for over 1 hr without recovery owing to small production rate during the evening. Chou et al, 2018), partly because the flight altitudes of Falcon Heavy (below 200 km) are below ionospheric F region. The value of TEC depletion is small (cf.…”
Section: Falcon Heavy Triggered Traveling Ionospheric Disturbancesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent publication, Chou et al [20] analyzed the ionospheric response to the 24 August 2017 Falcon 9 rocket launch from the Vandenberg Air Force Base in California. The fact that the second-stage engine continued burning throughout the 84-721 km altitude range allowed for a unique opportunity to study the interaction between the ionosphere and the rocket plume.…”
Section: Introductionmentioning
confidence: 99%